Prenatal vitamin D supplementation and child respiratory health: A systematic review and meta-analysis of randomized controlled trials - Amare Abera Tareke; Addis Alem Hadgu; Andualem Mossie Ayana; Taddese Alemu Zerfu (World Allergy Organization Journal, 2020)
Background: Systematic review and meta-analyses of observational studies on maternal vitamin D status and risk of respiratory allergic conditions indicated that mothers who had supplementation during pregnancy could decrease the risk of recurrent wheeze or asthma in their offspring. Objectives: We conducted this meta-analysis of Randomized Controlled Trials with the primary intention of detecting the effect of prenatal vitamin D supplementation on the offspring's asthma. Secondary outcomes under respiratory health include eczema, lower respiratory tract infections, Immunoglobulin E positive test, upper respiratory tract infections, and allergic rhinitis. Methods: A comprehensive search of PubMed, ScienceDirect, Google Scholar, and Cochrane Library databases was performed to retrieve randomized controlled trials. Risk Ratio with 95% confidence intervals was computed from dichotomous data using a random-effects model, with I2 >50% representing notable heterogeneity. Results: Six clinical trials met the inclusion criteria, involving a total of 2898 subjects (1461 experimental group and 1437 control group). There was non-significant inverse relationship between vitamin D intake during pregnancy and the occurrence of asthma in offspring (pooled RR = 0.89, 95% CI = 0.69–1.15, I2 = 46% and Z-static = 0.90, P-value = 0.37). There is no significant difference in the risk of assessed childhood respiratory problems due to maternal supplementation of vitamin D during pregnancy. Conclusion and implications: Currently, there is no fertile evidence to promote vitamin D supplementation in pregnancy for childhood respiratory health. Future clinical trials should emphasize early initiation of vitamin D supplementation, consider 6 weeks to 6 months postnatal critical window for vitamin D deficiency for offspring, lower risk dose of vitamin D, and identify different phenotypes of asthma and response to vitamin D supplementation.